2018
DOI: 10.1177/0031721718775680
|View full text |Cite
|
Sign up to set email alerts
|

What makes difficult history difficult?

Abstract: All modern nation-states have periods of difficult history that teachers fail to address or address inadequately. The authors present a framework for defining difficult histories and understanding what makes them difficult. These events 1) are central to a nation’s history, 2) contradict accepted histories or values, 3) connect with present problems, 4) involve violence enacted by the state or large groups of citizens, and 5) create disequilibria that require changes to historical understandings that may carry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 10 publications
1
28
0
5
Order By: Relevance
“…Many factors--sociocultural, historical, temporal--influence the degree to which a given event is understood to be difficult or traumatic, but my analytical interest falls in the space between violence understood to be "difficult" and violence treated as banal; both have serious implications for teachers and students as they create and interact with curriculum. I explore the relationship between historical violence and curriculum first by setting out "what makes difficult history difficult" (Gross & Terra, 2018) and then weighing the contributions of scholarship on teaching about violent histories in three contexts: the relationship between historical thinking and violence (with particular attention to issues of recency, proximity, and historical distance), the relationship between teachers and violence in curriculum, and finally, pedagogical concerns and approaches used with students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors--sociocultural, historical, temporal--influence the degree to which a given event is understood to be difficult or traumatic, but my analytical interest falls in the space between violence understood to be "difficult" and violence treated as banal; both have serious implications for teachers and students as they create and interact with curriculum. I explore the relationship between historical violence and curriculum first by setting out "what makes difficult history difficult" (Gross & Terra, 2018) and then weighing the contributions of scholarship on teaching about violent histories in three contexts: the relationship between historical thinking and violence (with particular attention to issues of recency, proximity, and historical distance), the relationship between teachers and violence in curriculum, and finally, pedagogical concerns and approaches used with students.…”
Section: Discussionmentioning
confidence: 99%
“…In David Lowenthal's (2015) return to his seminal work on conceptions of history, The Past is a Foreign Country: Revisited, he argues that thinking about the past presents three potential "evils," two of which have conditioned how people understand and make use of past suffering: "the concomitant griefs that the grievous past saddles on the present...and the menace of its continuing potency" (p. 129). The degree to which these concerns become salient is historically contingent--it matters when one considers the past as well as which past is under consideration--an insight that has profound influence on the lines drawn by Gross and Terra (2018) around what makes difficult history difficult in a given context or moment. Their framework situates violence as one of five criteria necessary to qualify as difficult history, the other four being: centrality to the history of a nation; refuting "broadly accepted versions of the past or stated national values"; relevance to contemporary problems; and creating "disequilibria that challenge existing historical understandings" (p. 54).…”
Section: Problems Of Difficulty and Aestheticizationmentioning
confidence: 99%
“…The formulations of Simon et al (2000), Zembylas and Bekerman (2008), and Gross and Terra (2018) make sense for filtering acts of historical violence through lenses of difficulty and trauma, but filtering historical violence on the basis of contemporary contextual resonance or state sanction implies that many-perhaps most-acts of historical violence that appear in curricula year after year may not qualify as "difficult" at a given moment. As Gross and Terra (2018) point out, If the difficulty of history is socially constructed, both outside the classroom and through the interactions of teachers and students with the curriculum, historical violence that is not deemed difficult may represent the majority of history curriculum in some contexts (particularly in teaching the history of the United States). With that in mind, it is troubling that the great weight of violence throughout history is understood to be (and taught as) untroubling.…”
Section: Problems Of Difficulty and Aestheticizationmentioning
confidence: 99%
“…Carretero (2017) does not explicitly address the issue of violence as bound up in the difficulties of historical distance (using "conflict" instead), but those issues certainly influence his argument for understanding and treating historical conflict in three separate contexts: academic history, school history, and popular history. While the interactions of those three types of historical discourse condition teacher decisions and student reactions to violence, for Carretero the key to understanding the "difficulty" of violence is uncovering the relationship between individuals and the state, an argument echoed by Gross and Terra (2018).…”
Section: Different Measures Of Historical Distancementioning
confidence: 99%
“…Then they might realize that the course of history is not fixed and that the outcomes could also have been different. This is not an easy task, as several studies have shown that having a debate in multicultural classrooms can be very demanding (Grever, 2012;Gross & Terra, 2018;Grever, 2018;Savenije, van Boxtel, & Grever, 2014). Students with different cultural backgrounds often have other, sometimes opposing, world views and conceptions of history.…”
Section: Opportunities For Historically Effected Consciousness In Hismentioning
confidence: 99%